Xiphoid horn in pectus excavatum. Issue 6 (November 1969) - Skinner, Edward F.
Abstract : In pectus excavatum there may be a cartilaginous horn on the inner surface of the xiphoid process rubbing on the heart, or the xiphoid process may be tipped inward, rubbing on the heart and causing anginoid pain. Being cartilaginous, these protrusions of the xiphoid cartilage are not visible on preoperative radiographs. Eight per cent of pectus excavatum patients have organic heart disease (Reusch, 1961). Funnel chest may cause anginoid pain (Poppe, 1965) which can be relieved surgically.